2020
DOI: 10.1177/2514848620941515
|View full text |Cite
|
Sign up to set email alerts
|

Policy framing and crisis narratives around food safety in Vietnam

Abstract: While progress has been made recently in understanding food systems per se, much less is known about policies around those food systems. In this paper, we aim at understanding the food system policy context with the specific objective to look at policy dynamics—defined as the way policy agendas are identified, justified, and framed by decision-makers, and how they interact. Vietnam is used as a case study. Primary data were generated through face-to-face interviews complemented by an online survey. A policy fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…The 'supermarketisation' of urban areas and cities is often viewed as a way to guarantee a regulated food system. However, traditional markets, such as wet markets, often represent an important and preferred food outlet in LMICs (Béné et al, 2020;Chuvileva et al, 2020;Figuié and Moustier, 2009). Therefore, the needs and preferences of low-income consumers is important to avoid the negative effects on purchase, consumption and livelihoods.…”
Section: Food Safety Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 'supermarketisation' of urban areas and cities is often viewed as a way to guarantee a regulated food system. However, traditional markets, such as wet markets, often represent an important and preferred food outlet in LMICs (Béné et al, 2020;Chuvileva et al, 2020;Figuié and Moustier, 2009). Therefore, the needs and preferences of low-income consumers is important to avoid the negative effects on purchase, consumption and livelihoods.…”
Section: Food Safety Findings and Discussionmentioning
confidence: 99%
“…It was surprising that only four studies discussed the need to combine food safety into policies and practices that focus on nutrition, chronic disease and overweight and obesity (Bastami et al, 2019;Blum et al, 2019;Trubswasser et al, 2020;Wertheim-Heck et al, 2019). Overlooking this focus in food safety research on consumer behavior should be particularly salient for increasing overweight/obesity polices and programming in LMICs (Béné et al, 2020;Shekar and Popkin, 2020).…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
“…Narratives of neoliberal market economics as being non-negotiable, and nutrition being an issue of individual responsibility, are regularly seen in work assessing these processes (Friel et al, 2020), as seen in the trade coalition in our work. Other assessments of narratives around trade and food in Vietnam have found that none of the narratives are around health or nutrition, rather everything is about aspects of economics, from protecting farmers and small business, to economic growth, to price stabilisation (Béné et al, 2020). In the other direction, engaging the trade coalition in discussions around nutrition issues may be difficult, as previous work has shown that trade experts in Vietnam see themselves as having engaged already in food system debates, whether or not they class themselves as knowledgeable about those debates; and trade actors feel that the current food system agenda (including trade) already matches reality in terms of food needs (Béné et al, 2020).…”
Section: Policy Space: Context and Issuesmentioning
confidence: 99%
“…Other assessments of narratives around trade and food in Vietnam have found that none of the narratives are around health or nutrition, rather everything is about aspects of economics, from protecting farmers and small business, to economic growth, to price stabilisation (Béné et al, 2020). In the other direction, engaging the trade coalition in discussions around nutrition issues may be difficult, as previous work has shown that trade experts in Vietnam see themselves as having engaged already in food system debates, whether or not they class themselves as knowledgeable about those debates; and trade actors feel that the current food system agenda (including trade) already matches reality in terms of food needs (Béné et al, 2020). The evidence in this paper, and evidence on changing diets in Vietnam (Harris et al, 2020), may be an entry point to discussions aimed at clarifying or changing these narratives.…”
Section: Policy Space: Context and Issuesmentioning
confidence: 99%
See 1 more Smart Citation